An experimental and numerical study of the light scattering properties of ice crystals with black carbon inclusions. (May 2018) - Arienti, Marco; Geier, Manfred; Yang, Xiaoyuan; Orcutt, John; Zenker, Jake; Brooks, Sarah D.
Highlights: New spectrometer data of forward scattering and backward polarization from ice crystals nucleated on BC particles under controlled conditions. Direct comparison with calculations of the scattering phase matrix using geometrical optics and discrete dipole approximation techniques. Data analysis suggests that the size of BC could play a role in determining the size and morphology of ice crystals that nucleate on them. Parametric calculations confirm the factor 1.5 as lower bound in absorption magnification even for off-center position of the BC inclusion. Analysis finds that simplification to perfectly spherical shape for the ice crystal causes exceedingly large variations of absorption magnification. Abstract: We investigate the optical properties of ice crystals nucleated on atmospheric black carbon (BC). The parameters examined in this study are the shape of the ice crystal, the volume fraction of the BC inclusion, and its location inside the crystal. We report on new spectrometer measurements of forward scattering and backward polarization from ice crystals nucleated on BC particles and grown under laboratory-controlled conditions. Data from the Cloud and Aerosol Spectrometer with Polarization (CASPOL) are used for direct comparison with single-particle calculations of the scattering phase matrix. Geometrical optics and discrete dipole approximation techniques are jointly used to provide the best compromise of flexibility and accuracy over a broad range of size parameters. Together with the interpretation of the trends revealed by the CASPOL measurements, the numerical results confirm previous reports on absorption cross-section magnification in the visible light range. Even taking into account effects of crystal shape and inclusion position, the ratio between absorption cross-section of the compound particle and the absorption cross-section of the BC inclusion alone (the absorption magnification) has a lower bound of 1.5; this value increases to 1.7 if the inclusion is centered with respect to the crystal. The simple model of BC-ice particle presented here also offers new insights on the effect of the relative position of the BC inclusion with respect to the crystal's outer surfaces, the shape of the crystal, and its size.